SYNTHESIS OF NANO MATERIALS BY MICROWAVE ASSISTED HYDROTHERMAL METHOD - Trital, Hiramani; Rajbhandari, Armila; Adhikari, Rajesh; Lee, Soo Wohn (Scientific World, 2015)
Bismuth tungstate nano materials have been successfully synthesized by microwave assisted hydrothermal method. Bismuth nitrate (Bi(NO3)3.5H2O) and sodium tungstate (Na2WO4.2H2O) are used as a starting material for the preparation of nano materials and solution pH was maintained to 3. The prepared material was characterized by X-ray diffraction (XRD) to study the phase state, whereas surface morphology was observed by Scanning Electron Microscopy (SEM). The surface area was determined by Brunauer-Emmett-Teller (BET) method. The results revealed that materials are crystalline in nature having crystallite size of ~ 24 nm with surface area of 6.5 m2/g. SEM image of prepared materials showed a unique discrete hierarchical morphology. The prepared material showed visible light active photocatalytic nature for the decomposition of Rhodamine B. Scientific World, Vol. 12, No. 12, September 2014, page 21-23